Kajian Distribusi Perekat Pada Pembuatan Papan Partikel - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT The objectives of the research entitled the study of resin distribution in par- ticleboard processing are as follows: 1). to obtain the resin spread pattern on the surface of particles due to different atomization pressure or spraying pressure, 2). to observe the resin distribution influenced by air sprayer types and 3). to evaluate the particles internal bonding resulting from specific spraying method. Factors involved in resin spraying seem to be neglected due to some reasons. The research was completed by conducting 4 sub-experiments, namely sub-experiment on particle dimension resulted by three levels specific setting of the planer, sub-experiment on resin distribution in different particle dimension